Disseminated superficial actinic porokeratosis - Dhillon, K. S.; Sharma, Deepak; Singh, Tarunveer; Srivasatva, Sweksha; Srivastava, Ritika; Khan, Areeba; Yadav, Soni; Agarwal, Vidhi (International Journal of Advances in Medicine, 2017)
Disseminated Superficial Actinic Porokeratosis (DSAP) is a type of porokeratosis observed in parts of the skin exposed to intense sunlight and usually appears in the third or fourth decade of life. We are presenting a case report of a 30 year old male patient presenting with multiple lesions over the face and limbs.